Boosting the Performance of Graphene Cathodes in Na–O2 Batteries by Exploiting the Multifunctional Character of Small Biomolecules. Issue 2 (16th December 2020) - Enterría, Marina; Gómez‐Urbano, Juan Luis; Munuera, Jose María; Villar‐Rodil, Silvia; Carriazo, Daniel; Paredes, Juan Ignacio; Ortiz‐Vitoriano, Nagore
Abstract: Graphene aerogels derived from a biomolecule‐assisted aqueous electrochemical exfoliation route are explored as cathode materials in sodium–oxygen (Na–O2 ) batteries. To this end, the natural nucleotide adenosine monophosphate (AMP) is used in the multiple roles of exfoliating electrolyte, aqueous dispersant, and functionalizing agent to access high quality, electrocatalytically active graphene nanosheets in colloidal suspension (bioinks). The surface phenomena occurring on the electrochemically derived graphene cathode is thoroughly studied to understand and optimize its electrochemical performance, where a cooperative effect between the nitrogen atoms and phosphates from the AMP molecules is demonstrated. Moreover, the role of the nitrogen atoms in the adenine nucleobase of AMP and short‐chain phosphate is unraveled. Significantly, the use of such cathodes with a proper amount of AMP molecules adsorbed on the graphene nanosheets delivers a discharge capacity as high as 9.6 mAh cm −2 and performs almost 100 cycles with a considerably reduced cell overpotential and a coulombic efficiency of ≈ 97% at high current density (0.2 mA cm −2 ). This study opens a path toward the development of environmentally friendly air cathodes by the use of natural nucleotides which offers a great opportunity to explore and manufacture bioinspired cathodes for metal–oxygen batteries. Abstract : Graphene air cathode containing a natural nucleotide adenosine monophosphate (AMP) for Na–O2 batteries is reported. This molecule presents multiple roles: exfoliating electrolyte, aqueous dispersant, and functionalizing agent. Moreover, the nitrogen‐containing nucleobase and the acidic POH sites in orthophosphates from AMP work cooperatively to promote the nucleation of NaO2 during discharge while enhancing its dissolution during charge.